Vitamin D Deficiency Linked To Depression (Systematic Review: Meta Synthesis) - Talitha Salsabila; Indranila Kustarini Samsuria; Dwi Retnoningrum; Indah Saraswati (JURNAL KEDOKTERAN DIPONEGORO (DIPONEGORO MEDICAL JOURNAL), 2021)
Background: Depression is a mood disorder that is marked by a persistent feeling of sadness, loss of interest; reduced energy and vitality; feelings of low self-worth or guilt; loss of appetite; disturbed sleep or insomnia; and slowness of thought or action. Vitamin D deficiency has been associated with depression. When the level of Vitamin D and serotonin is low, that leads to depression.Objective: To analyze whether vitamin D deficiency or insufficiency is associated with depression.Method: This is a Systematic Review Report. Samples were gathered from two journals – PubMed and Science Direct with specific search terms used were 'vitamin D' and 'depression', then were adjusted based on the inclusion criteria and research question. After that, the findings are combined in order to reach a conclusion so that the research question is well answered.Results: There are eleven journals that describe a link between low level of Vitamin D and symptoms of depression. The connection between the two is formed due to the neuroprotector and immunomodulatory effects of Vitamin D.Conclusion: Previous studies have shown that Vitamin D deficiency linked to depression. Keywords : Depression, level of vitamin D, vitamin D serum.